SUSTAINABILITY ACCOUNTING CAPABILITIES IN MSMES: CONNECTING ENVIRONMENTAL INFORMATION, MANAGERIAL JUDGMENT, AND LONG-TERM VALUE CREATION - Nia Riana; Raden Roro Fatmasari (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual and integrative review develops a framework for sustainability accounting capability in micro, small, and medium enterprises. It addresses the problem that many MSMEs face growing sustainability expectations but lack proportionate systems for translating environmental and social information into operational and financial decisions. Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, and resilience, the paper explains how materiality assessment, resource-use accounting, stakeholder dialogue, integrated decision routines, learning-oriented disclosure can be organized as mutually reinforcing routines. The proposed pathway moves from problem diagnosis and capability mapping to bounded experimentation, evidence review, resource reconfiguration, and learning retention. No primary survey, interview, experimental, administrative, or statistical data are claimed. The framework links these mechanisms to information relevance, cost awareness, stakeholder legitimacy, decision quality, long-term value creation and identifies managerial, institutional, and research implications suitable for resource-constrained enterprises.